Media Affordance in Digital Dakwah: A Study of Religious Communication Practices in Social Media - Saidah, Musfiah (Ultimacomm: Jurnal Ilmu Komunikasi, 2024)
This research examines the use of multimedia content in digital da'wah, with a focus on religious communication practices on social media. With the development of information and communication technology, da'wah via social media has become an increasingly popular strategy among preachers to reach a wider audience. This study explores various forms of multimedia content, such as videos, images, infographics and animations, and how these contents are used to convey religious messages. The research methodology used consists of content analysis and interviews with preachers who are active on social media. The research results show that multimedia content is effective in attracting attention and increasing audience understanding of da'wah material. In addition, interactions that occur on social media provide space for constructive dialogue between preachers and audiences. However, this research also found challenges faced, including the issue of credibility of information and the misuse of social media to spread ideas that are not in accordance with religious teachings. The conclusions of this research emphasize the importance of appropriate communication strategies and the use of quality multimedia content in digital da'wah to maximize the positive impact on society.